حمــاية الشهود في ضوء التشريعات الوطنية والدولية - مرين, يوسف; عباسة, طاهر (Revue jurisprudence, 2018)
يتشجع الشاهد ويقدم على الإدلاء بشهادته عندما يشعر بالأمان على نفسه وعلى عائلته وأقاربه من بعده، أما إذا كان هنالك خطر يهدده بسبب إدلائه بشهادته فإنه سوف يحجم عنها وربما يصل الأمر به إلى الامتناع عن الحضور أو قلب الموازين إذا حضر لصالح المجرم خوفا من بطشه على نفسه أو على أقاربه. وفي كثير من الأحيان تقع جرائم على قدر كبير من الخطورة، ويكون مرتكبوها ذوي بطش ونفوذ فإذا وقعت مثل هذه الجرائم فإن الكثير من الأشخاص أو الضحايا يحجم عن الإدلاء بأية معلومة عنها بسبب الخوف من بطش مرتكبيها. لهذا ظلت قضية إحجام الشهود عن الشهادة تشغل اهتمام العديد من العاملين في القانون، وحاولت بعض التشريعات الوطنية والدولية الاجتهاد في وضع الحلول لذلك، ومن بين تلك الحلول التي تم الإجتهاد في وضعها إيجاد تدابير حماية لهم. الكلمات المفتاحية: الشهود، الخبراء، الضحايا، أمن الشهود والخبراء، التدابير الإجرائية وغير الإجرائية. Abstract : The witness and be encouraged to testify when it feels safe to himself and his family and relatives from beyond, if there is the risk of threatened because of his testimony, it would be reluctant to and perhaps to refrain from attendance or the heart of the balances if the offender attended for fear of has stubbornly rejected to himself or his relatives. In many cases, the crimes of great seriousness, and perpetrators of brutality and influence if such crimes, many of the persons or victims refrain from giving any information due to fear of persecution of the perpetrators. This issue has been the reluctance of witnesses to testify occupy the attention of many workers in the law, and tried some national legislation and international jurisprudence in the development of solutions, and those solutions that stress in developed find measures to protect them. Keywords: Witnesses, experts, amounts, the security of witnesses and experts, and non-procedural measures.